Utilization of mieki as an alternative to yeast extract in batch ethanol fermentation - Fathurrahman, Lananan (Universiti Malaysia Sarawak, UNIMAS, 2009)
In standard ethanol fermentation, yeast extract (YE) had been recognized as the most important component vital for microbial nitrogen supply, functions as growth promoter. However, yeast extract is very expensive to be applied in fermentation. Thus, a study was done with the aim in utilizing Mieki (ME) as an alternative compound to yeast extract for significant cost reduction especially in fermentation research field and ethanol production industry. Establishment of glucose standard curve was done with 30 replicates using DNS methods by Sumner, 1921 and Miller, 1959 which yield Y-value, 2.5353 and r2-value, 0.9905. Batch ethanol fermentations were performed using 100g/L dextrose inoculated with 1% (v/v) Saccharomyces cerevisiae CSI-1 JCM15097 and proceeded for 24H. Two replicates of batch ethanol fermentation with 5g/L YE, four replicates of 2% (v/v) ME, and each for 4%, 8% and 10% (v/v) ME respectively. YE proved to show the best ethanol yield, 49.65g/L; followed by 2% (v/v) ME, 34.40g/L; and steady decline with the increase of concentration of Mieki to 10% (v/v) ME, 18.60g/L in 24H period. Performances of ME and YE for 36H onwards were comparable; 46.39g/L and 47.26g/L ethanol yield respectively.